Demand-driven corporate social responsibility: Symbolic versus substantive change after environmental disasters - García Lara, Juan Manuel; García Osma, Beatriz; Gazizova, Irina; Khalilov, Akram (Journal of Corporate Finance, 2025)
We examine disasters caused by individual firms with severe environmental impacts. These disasters trigger industry-wide demand for corporate social responsibility (CSR). We analyze whether affected firms respond by adopting substantive or symbolic CSR measures. We find that firms increase overall CSR performance through improvements in diversity and human rights rather than decreasing environmental concerns. This suggests firms prioritize symbolic CSR to legitimize their operations rather than substantive measures to mitigate environmental harm. We also document diverging costs and welfare effects. On average, substantive CSR actions are costlier and cause lower margins but avoid divestments by ESG-oriented funds while improving long-term credit ratings. Some of these benefits of substantive actions also accrue through symbolic actions at a lower cost.